Factor contribute personal finance planning among KKTM Pasir Mas students / Rose Shalizan Mat Rifin - Mat Rifin, Rose Shalizan (Bachelor of Science (Hons.) Statistics, 2013)
This paper explores about the relationship between students‟ financial planning with attitude, awareness, and behaviour. The purpose of this study is to determine the relationship between attitude, awareness, and behaviour with personal finance planning. This study uses primary data base. The data has been collected by self-administration questioner from Kolej Kemahiran Tinggi Mara (KKTM) Pasir Mas on 150 respondents and being tested by using regression analysis. The Pearson correlation and multiple regression analysis were employed to measure whether the independent variable have signification relationship with the dependent variable